Revision of the extant Nearctic species of Dryinus Latreille 1804 group 1 (Hymenoptera: Dryinidae), with description of a new species from the USA - Guglielmino, Adalgisa; Olmi, Massimo (Zootaxa, 2013)
The extant Nearctic species of Dryinus Latreille, 1804 group 1 are revised. A new species is described from the USA, New Mexico, Eddy County: D. splendidus Guglielmino & Olmi, sp. nov. A new combination is proposed for D. wetmorei (Olmi, 1984), comb. nov. (from Richardsidryinus Móczár). A new key to the females of the extant Nearctic species of Dryinus group 1 is presented.